The Legal Regulation of Energy Efficiency and Energy Saving Policies in the Republic of Kazakhstan - Kozhukhova, Madina; Amanzholova, Botagoz; Zhiyenbayev, Miras (International Journal of Energy Economics and Policy, 2019)
The paper focuses on one of the main challenges of Kazakhstan’s economy – its high energy intensity of GDP. Contemporary scholarship states that high energy intensity of GDP is a common characteristic of almost all post-Soviet countries, which are also very affected by weak institutions and under-developed legal frameworks in the fuel and energy sectors. The paper analyzes the legal framework existing in Kazakhstan, the largest economy of Central Asia, with respect to energy efficiency and energy saving policies, which are considered a sufficient way of reducing energy intensity of GDP. A total of seven key documents adopted in 2010-2014 are carefully reviewed, which comprise the legal foundation of Kazakhstan’s energy efficient economy. The paper also presents a “pyramid” of energy efficiency and energy saving development of Kazakhstan, on the bottom of which is the legal framework, based on the results of our analysis. Keywords: legal framework, energy efficiency, Kazakhstan. JEL Classifications: E60, Q42, Q43, Q48 DOI: https://doi.org/10.32479/ijeep.7550